VD_FINDINFO Décision / 2015 / 175 vom 26. Januar 2015 - VD Tribunal cantonal (2015)
DÉFENSE D'OFFICE, REJET DE LA DEMANDE | 130 let. b CPP (CH), 132 al. 1 let. b CPP (CH), 132 al. 2 CPP (CH), 132 al. 3 CPP (CH)